Formulation and Evaluation of Cubosomal In-Situ Gel for Topical Aaplication - Gangasagar B., Kardile; N. Nagoba, Shivappa; N. Humnabade, Shital; C. Kakade, Sneha (Journal of Neonatal Surgery, 2025)
Background: Nanotechnology has emerged as a transformative approach in drug delivery, particularly for enhancing the therapeutic efficacy and targeting of poorly soluble drugs.The present study focuses on the formulation and evaluation of a thermosensitive cubosomal in-situ gel for the vaginal delivery of voriconazole, aimed at enhancing local antifungal therapy. Methods: Cubosomes were prepared using the thin film hydration method incorporating voriconazole, poloxamer 188, GMO and a suitable solvent, followed by hydration with distilled water to form a stable cubosomal dispersion. The dispersion was further integrated into an in-situ gel system using thermosensitive polymers Poloxamer 407 and Carbopol 940P prepared under cold conditions (2–8°C) to prevent premature gelation. Results: Among the formulations, VF5 exhibited superior cubosomal characteristics with a drug content of 78.88%, entrapment efficiency of 73.24% and in-vitrodrug diffusion 77.72% at 12 hours. Particle size analysis showed a Z-average of 102.0nm, PDI at 0.381 and Zeta potential at -10.2 mV, indicating good stability. Upon incorporation into the in-situ gel, formulation V2 demonstrated optimal physicochemical properties, including a pH at 5.4, Viscosity at 1128.33±12.89 cps and excellent spreadability. Gelation temperature was found to be 36±0.30°C with strong gel strength (+++) and a gelation time of 11seconds. V2 also showed the highest Drug Content (81.84%), Entrapment Efficiency (73.93%) and Drug Diffusion (79.57% at 12hrs) highlighting its potential as an effective topical drug delivery system. Conclusion: These findings suggest that the cubosomalin-situ gel system offers a promising platform for controlled and targeted delivery of antifungal agents.